Stearoyl-CoA desaturase-1 impairs the reparative properties of macrophages and microglia in the brain - Bogie, Jeroen F J; Grajchen, Elien; Wouters, Elien; Corrales, Aida Garcia; Dierckx, Tess; Vanherle, Sam; Mailleux, Jo; Gervois, Pascal; Wolfs, Esther; Dehairs, Jonas; Van Broeckhoven, Jana; Bowman, Andrew P; et al. (The Journal of experimental medicine, 2020)
Failure of remyelination underlies the progressive nature of demyelinating diseases such as multiple sclerosis. Macrophages and microglia are crucially involved in the formation and repair of demyelinated lesions. Here we show that myelin uptake temporarily skewed these phagocytes toward a disease-resolving phenotype, while sustained intracellular accumulation of myelin induced a lesion-promoting phenotype. This phenotypic shift was controlled by stearoyl-CoA desaturase-1 (SCD1), an enzyme responsible for the desaturation of saturated fatty acids. Monounsaturated fatty acids generated by SCD1 reduced the surface abundance of the cholesterol efflux transporter ABCA1, which in turn promoted lipid accumulation and induced an inflammatory phagocyte phenotype. Pharmacological inhibition or phagocyte-specific deficiency of Scd1 accelerated remyelination ex vivo and in vivo. These findings identify SCD1 as a novel therapeutic target to promote remyelination.